Cost-utility of 20-valent pneumococcal conjugate vaccine compared to no vaccination and recommended alternative vaccines among Belgian adults - Sophie Marbaix; Annick Mignon; Audrey Taelman; Ahuva Averin; Mark Atwood; Jeffrey Vietri (Taylor & Francis Group, 2023)
Background The Belgian Superior Health Council (SHC) preferentially recommended the 20-valent pneumococcal conjugate vaccine (PCV20) for adults aged ≥65 years, immunocompromised patients, and patients aged ≥50 years suffering from conditions that increase their risk for pneumococcal infections. The objective of this paper is to present the cost-utility of PCV20 compared to no vaccination and the alternative sequence of PCV15 followed by the 23-valent pneumococcal polysaccharide vaccine (PPV23) in this population. Research Design and Methods The analysis employed a static Markov model capturing lifetime risk of pneumococcal infections, associated disutility, mortality and costs from different healthcare payer perspectives. Results Results indicated use of PCV20 among Belgian older and at-risk adults is highly cost-effective compared to no vaccination, with an incremental cost per quality-adjusted life-year (QALY) of €4,164. Compared to the sequential regimen (PCV15+PPV23), PCV20 vaccination is a cost-saving strategy. Subgroup analysis indicated PCV20 vaccination of at-risk adults aged 65-84 years would also be cost-saving from the national healthcare perspective. Conclusion Based on current knowledge, this analysis suggests that access to PCV20 should be proposed in all adults recommended for vaccination by the SHC as PCV20 prevents additional hospitalizations and deaths caused by pneumococcal infection at an affordable cost.